Combination of Primary Hemostatic Disorders and Atrial Fibrillation Increases Bleeding Events Following Transcatheter Aortic Valve Replacement - Matsushita, Kensuke; Marchandot, Benjamin; Kibler, Marion; Carmona, Adrien; Phi, Truong Dinh; Heger, Joe; Trimaille, Antonin; Hess, Sébastien; Sattler, Laurent; Ohana, Mickael; Reydel, Antje; Jesel, Laurence; Ohlmann, Patrick; Morel, Olivier (TH Open, 2023)
Background Patients with atrial fibrillation (AF) are likely to have a poor prognosis including bleedings following transcatheter aortic valve replacement (TAVR). Closure time of adenosine diphosphate (CT-ADP) is a primary hemostasis point-of-care test and is a predictor of bleeding events following TAVR. We aimed to evaluate the impact of ongoing primary hemostatic disorders on bleeding events in TAVR patients with AF.Methods We enrolled 878 patients from our prospective registry. The primary endpoint was VARC-2 major/life-threatening bleeding complications (MLBCs) at 1 year after TAVR and secondary endpoint was major adverse cardiac and cerebrovascular events (MACCEs) at 1 year, defined as a composite of all-cause death, myocardial infarction, stroke, and heart failure hospitalization. Ongoing primary hemostatic disorder was defined by a postprocedural CT-ADP >180 seconds.Results Patients with AF had a higher incidence of MLBCs (20 vs. 12%, p = 0.002), MACCE (29 vs. 20%, p = 0.002), and all-cause mortality (15 vs. 8%, p = 0.002) within 1 year compared to non-AF patients. When the cohort was split into four subgroups according to AF and CT-ADP >180 seconds, patients with AF and CT-ADP >180 seconds had the highest risk of MLBCs and MACCE. Multivariate Cox regression analysis confirmed that the patients with AF and CT-ADP >180 seconds had 3.9-fold higher risk of MLBCs, whereas those patients were no longer associated with MACCE after the adjustment.Conclusion In TAVR patients, AF with postprocedural CT-ADP >180 seconds was strongly associated with MLBCs following TAVR. Our study suggests that persistent primary hemostatic disorders contribute to a higher risk of bleeding events particularly in AF patients.
Keywords: transcatheter aortic valve replacement; atrial fibrillation; closure time of adenosine diphosphate; primary hemostasis; bleeding events